0
$\begingroup$

Prove that if $g:\mathbb{N}\rightarrow \mathbb{N}$ and $\forall x,y\in \mathbb{N}, x<y\Rightarrow g(x)<g(y)$ then $n\leq g(n)\space\space\space \forall n\in \mathbb{N}$

My proof so far (induction): It's tru for 1 since 1 is less or equal any number in $\mathbb{N}$.

Let's suppose for $k$, $k\leq g(k)$, we got this:

$$k<k+1\Rightarrow g(k)<g(k+1)$$ so, $k\leq g(k)<g(k+1)$ And then I don't know what else to do. As far as I understand the operation "$-$" isn't defined yet for $\mathbb{N}$.

$\endgroup$
  • $\begingroup$ I've been suggested to use this property (which im not sure it actually exists) "if $k<g(k+1)$ then $k+1\leq g(k+1)$" $\endgroup$ – José Osorio Jun 10 '16 at 5:59
  • $\begingroup$ nope, it is strict. (why? do you think the problem is wrong? $\endgroup$ – José Osorio Jun 10 '16 at 6:04
  • 1
    $\begingroup$ I can see why $g(x) < g(y)$ must be a strict inequality, but you need to have "then $n \leq g(n)$", since $g(n) = n$ fulfills the requirements. $\endgroup$ – Arthur Jun 10 '16 at 6:09
  • $\begingroup$ if $n<g(n)$ , you need to suppose $k<g(k)$ and not $k\leq g(k)$ $\endgroup$ – user160823 Jun 10 '16 at 6:12
1
$\begingroup$

You're very close. Since $k < g(k+1)$, we must have $k+1 \leq g(k+1)$, since there are no numbers between $k$ and $k+1$. That finishes the induction step.

Together with my comment above that the problem needs to read "then $n \leq g(n)$" because of the function $g(n) = n$, the problem is now solved.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.